Synthesis of a N-Phthilimido & Acetylated tyrosine for tyrosinase inhibitory activity - R. SRINIVASAN; C.UMA MAHESWARA REDDY; B.JAYAKAR (International Journal of Pharma and Bio Sciences, 2011)
The present study deals with the application of α N-Phthilimido and acetylated tyrosine and determination of tyrosinase inhibitory activity which serves as an useful target in the treatment of hyper pigmentation skin disorder. The tyrosinase inhibitory activity of α N-Phthilimido tyrosine found to be highly significant (p< 0.0001) when compared with that of acetyltyrosine